Radiation-induced cxcl12 upregulation via histone modification at the promoter in the tumor microenvironment of hepatocellular carcinoma - Ahn, Hak Jun; Hwang, Soon Young; Nguyen, Ngoc Hoan; Lee, Ik Jae; Lee, Eun Jeong; Seong, Jinsil; Lee, Jong Soo (Molecules and Cells, 2019)
Tumor cells can vary epigenetically during ionizing irradiation (IR) treatment. These epigenetic variegations can influence IR response and shape tumor aggressiveness. However, epigenetic disturbance of histones after IR, implicating in IR responsiveness, has been elusive. Here, we investigate whether altered histone modification after IR can influence radiation responsiveness. The oncogenic CXCL12 mRNA and protein were more highly expressed in residual cancer cells from a hepatoma heterotopic murine tumor microenvironment and coculture of human hepatoma Huh7 and normal IMR90 cells after radiation. H3K4 methylation was also enriched and H3K9 methylation was decreased at its promoter region. Accordingly, invasiveness and the subpopulation of aggressive CD133+/CD24– cells increased after IR. Histone demethylase inhibitor IOX1 attenuated CXCL12 expression and the malignant subpopulation, suggesting that responses to IR can be partially mediated via histone modifications. Taken together, radiation-induced histone alterations at the CXCL12 promoter in hepatoma cells are linked to CXCL12 upregulation and increased aggressiveness in the tumor microenvironment.
Keywords: Animals; Carcinoma, Hepatocellular; CCAAT-Enhancer-Binding Protein-beta; Cell Line, Tumor; Cell Survival; Chemokine CXCL12; Epigenesis, Genetic; Gene Expression Regulation, Neoplastic; Heterocyclic Compounds; Histones; Humans; Liver Neoplasms; Male; Mice; Mice, Nude; Neoplastic Stem Cells; Promoter Regions, Genetic; Protein Processing, Post-Translational; Receptors, CXCR4; Recombinant Proteins; Transcription, Genetic; Tumor Microenvironment; Up-Regulation; X-Rays; CXCL12; Histone modification; Malignancy; Radiation; Tumor microenvironment